Knowledge mapping of nano drug delivery systems across blood - Brain barrier from 1996 to 2022: A bibliometric analysis - Dayuan Zhong; Zhenyu Gan; Mengxue Zheng; Lan Li; Hui Cheng; Hongsheng Luo; Deliang Liu; Pingwen Liu; Huanjie Li; Xueming Ou; Yihui Deng (Heliyon, 2023)
Background: The blood-brain barrier (BBB) is a natural physiological barrier that protects the central nervous system from foreign substances and limits the delivery of drugs to the brain. Nanotechnology has opened up new possibilities for drug delivery in the brain. Over several decades, various Nanoparticle Drug Delivery Systems (NDDS) that can cross the BBB have been developed for targeted delivery in the brain. To gain a comprehensive understanding of the current research hotspots and trends of NDDS across the BBB, this paper employs bibliometric analysis of articles published in the core database of Web of Science (WOS) from 1996 to 2022. Method: A search for relevant research literature on NDDS that can cross the BBB was conducted in the Web of Science database, covering the period from 1996 to 2022. The Bibliometrix R-4.0 software package was used to analyze data related to the countries of publication, research institutions, journals, citations, and keywords. The analysis aimed to identify the co-occurrence of keywords in the documents, including their titles and abstracts. Additionally, cooperative network analyses of authors, institutions, and countries of publication were conducted. Results: A total of 436 articles were analyzed, originating from 174 journals and 13 books, with the majority published in Q1 and Q2 journals. Contributors from 53 countries or regions participated in the publication of these articles, with China, the United States, and India having the highest number of articles by correspondent authors, and China, the United States, and Germany being the most cited countries. Fudan University, Hacettepe University, and Sichuan University were the top three institutions with the most publications. Among the 436 articles analyzed, 1337 keywords and 1450 keywords plus were identified. Factor analysis grouped the keywords plus into two categories: drug delivery systems, polymeric nanoparticles, gold nanoparticles, transferrin, and others, and drug, delivery, efficiency, expression, and mechanism. Conclusion: The research on NDDS that can cross the BBB is gradually receiving attention, and the recognition and cooperation in this field have increased.